EXTENSION OF MCDM METHOD FOR SUPPLIER SELECTION PROBLEM WITH INTERVAL NUMBERS BASED ON OBJECTIVE WEIGHTING - Safari, Hossein; Jafarzadeh, Abdol Hossein; Aliahmadi, Mohammad Hadi; Fathi, Mohammad Reza (International Journal of Industrial Engineering: Theory, Applications and Practice, 2019)
Selecting the most appropriate supplier is considered to be the main primary concern in supply chain because the producers spend most of their time on supplying the raw materials and spare parts. Moreover a lion’s share of cost is allocated to buying goods and services. During the past years there were many methods to evaluate and select the suppliers but traditional models of supplier selection were based on quantitative data and they paid less attention to qualitative and imprecise data. In this paper a compromise solution of interval VIKOR is presented to develop a method for evaluating and selecting the appropriate suppliers. On the other hand, the objective weights based on Shannon entropy which is fitted with imprecise data are used to eliminate the mental error caused by subjective judgment. At the end a numerical example is presented to demonstrate the application of proposed method in selecting the suppliers.